Effective processes for arc-plasma treatment in large vacuum chambers of technological facilities - Borisov D. P.; Koval N. N. Nikolay Nikolaevich; Korotaev A. D.; Kuznetsov V. M.; Romanov V. Y.; Terekhov P. A.; Chulkov E. V. (2013, 2013)
Title screen